2014
DOI: 10.1074/jbc.m114.557751
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Structure and Function of 7SK Small Nuclear Ribonucleoprotein (snRNP) in Cells

Abstract: Background: HEXIM1 and LaRP7 bind to 7SK snRNA. Results: HEXIM1 and LaRP7 activation domain chimeras activated plasmid targets via defined 7SK snRNA motifs in cells. Conclusion: Specific RNA targets of HEXIM1 and LaRP7 and inhibition of P-TEFb were dissected genetically in vivo. Significance: This system facilitates studies of 7SK snRNP in cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 55 publications
2
23
1
Order By: Relevance
“…This contains the 211-217 acidic sequence that was hypothesized to induce an auto-inhibitory conformation of HEXIM (20). Such direct binding to RNA of a downstream sequence was contradicted recently by Peterlin and colleagues, who used an elegant approach in vivo to show that while truncated HEXIM 150-177 (comparable to the ARM peptide 149-179) and 150-220 were able to bind the HP1 RNA in vivo, the sequence 178-220, downstream of the ARM, was not binding the RNA (15). Models like those presented in Figure 3D or 3E may reconcile these observations.…”
Section: Two Hexim Monomers But Only One Arm Bind One Hp1 Hairpin Omentioning
confidence: 88%
See 3 more Smart Citations
“…This contains the 211-217 acidic sequence that was hypothesized to induce an auto-inhibitory conformation of HEXIM (20). Such direct binding to RNA of a downstream sequence was contradicted recently by Peterlin and colleagues, who used an elegant approach in vivo to show that while truncated HEXIM 150-177 (comparable to the ARM peptide 149-179) and 150-220 were able to bind the HP1 RNA in vivo, the sequence 178-220, downstream of the ARM, was not binding the RNA (15). Models like those presented in Figure 3D or 3E may reconcile these observations.…”
Section: Two Hexim Monomers But Only One Arm Bind One Hp1 Hairpin Omentioning
confidence: 88%
“…The linkage essentially established by the coiled-coil interface may be completed by interactions involving the acidic regions (as in Figure 3E). Linking the monomers could help increase the local concentration of the second monomer, thus facilitating the second binding to a weaker binding site Recent evidence for a second HEXIM-binding site comprised in the apical loop of HP1 (15) contrasts with the early experiments of Egloff et al (31), and the fact that this loop is not conserved (29). Another site was proposed at the basal stem of a 5'-hairpin comprising nucleotides 1-108 (24).…”
Section: Two Hexim Monomers But Only One Arm Bind One Hp1 Hairpin Omentioning
confidence: 91%
See 2 more Smart Citations
“…1A). Previously, we demonstrated that the chimeric CDK9.CycT1 protein is folded into a biologically functional P-TEFb complex (22,24). P-TEFb interacts with the CTD via its CycT1 subunit (12).…”
Section: Hybrid Ycp-tefb Proteins Are Incorporated Into the 7sk Snrnmentioning
confidence: 99%